IMPLIKASI PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PERUSAHAAN - Anjarwi, Astri Warih (FIA UB, 2019)
Basically, such practice is not in the favor of both the company and the emiten, for the published information is unreliable thus threatens the sustainability of the company. Tax planning is a means of tax management used for estimating the amount of tax that needs to be paid and other efforts to avoid tax reliability. This research builds upon tax planning motives that drive companies to save on tax responsibility that is an illegal action. Therefore, the management of a company will apply different tax management techniques to achieve its target. In addition to tax planning, tax responsibility also determines the practice of profit management. In order to save or defer tax payment, a company tends to submit a lesser profit report. This is done by manipulating the tax responsibility, thus, allow to conduct a profit management. This research aims at testing the impact of tax planning and tax responsibility on profit management. The research adopts a qualitative approach in reviewing annual reports of major public companies registered to the Indonesian Stock Exchange 2016-2017. It shows that tax planning and tax responsibility do not hold significant correlation on a companyâ€™s profit management.Â Â